Percutaneous tracheostomy in the COVID-19 era: have things changed? (Revista Argentina de Cirugía, 2026)
Background: Percutaneous tracheostomy (PT) is the preferred option in patients who require prolonged ventilatory support.Objective: The aim of this study was to estimate and compare the clinical variables in patients undergoing percutaneous tracheostomy in the pre-pandemic and pandemic COVID-19 periods.Materials and methods: We conducted a retrospective cohort study of patients who underwent percutaneous tracheostomy in the pre-pandemic period from October 2018 to February 2020, and in the pandemic period from March 2020 to July 2021.Results: A total of 35 patients required percutaneous tracheostomies,14 without SARS-CoV-2 infection and 21 with COVID-19. Mean age was 59 ± 12 years and 18 were men. There were no significant differences in age, sex and presence of comorbidities between both periods. Ten patients underwent scheduled decannulation, 2 (20%) without COVID-19 and 8 (80%) with COVID-19. Mean says spent on mechanical ventilation (MV) until scheduled decannulation was 51 days.Twenty-one patients died: 7 without COVID-19 and 14 with the disease. Two patients require reintubation/recannulation, 1 without COVID 19 and 1 with the disease. Complications occurred in 4 patients, 1 without COVID-19 and 3 with COVID-19.Mean days spent on MV was 37 and 39 days in patients without and with the disease, respectively. Conclusion: There were no statistically significant differences between the variables compared in both periods, possibly due to the sample size, despite the differences in mortality, percentage of decannulation and time spent on MV.
Keywords: COVID-19; SARS-CoV-2; percutaneous tracheostomy; MV